MXene-based flexible sensors: A review - Hajian, Sajjad; Maddipatla, Dinesh; Narakathu, Binu B.; Atashbar, Massood Z. (Frontiers in Sensors, 2022)
MXenes are an emerging family of two-dimensional (2D) materials which exhibits unique characteristics such as metal-like thermal and electrical conductivity, huge surface area, biocompatibility, low toxicity, excellent electrochemical performance, remarkable chemical stability, antibacterial activity, and hydrophilicity. Initially, MXene materials were synthesized by selectively etching metal layers from MAX phases, layered transition metal carbides, and carbonitrides with hydrofluoric acid. Multiple novel synthesis methods have since been developed for the creation of MXenes with improved surface chemistries using non-aqueous etchants, molten salts, fluoride salts, and various acid halogens. Due to the promising potential of MXenes, they have emerged as attractive 2D materials with applications in various fields such as energy storage, sensing, and biomedical. This review provides a comprehensive overview of MXenes and discusses the synthesis and properties of MXenes, including the methods of etching, delamination, and modiﬁcation/functionalization, as well as the electrical properties of MXenes. Following this, the recent advances in the development of various MXene-based sensors are presented. Finally, the challenges and opportunities for future research on the development of MXenes-based sensors are discussed.